2015
DOI: 10.1088/0004-637x/814/1/10
|View full text |Cite
|
Sign up to set email alerts
|

GRB 131014A: A LABORATORY FOR STUDYING THE THERMAL-LIKE AND NON-THERMAL EMISSIONS IN GAMMA-RAY BURSTS, AND THE NEW ${L}_{{\rm{i}}}^{\mathrm{nTh}}-{E}_{\mathrm{peak},{\rm{i}}}^{\mathrm{nTh},\mathrm{rest}}$ RELATION

Abstract: Over the past years, evidence has been accumulated on the existence of a thermal-like component during the prompt phase of Gamma Ray Bursts (GRBs). However, this component, often associated with the GRB jet's photosphere, is usually subdominant compared to a much stronger non-thermal one. The prompt emission of GRB 131014A-detected by the Fermi Gamma-ray Space Telescope (hereafter Fermi)-provides an unique opportunity to trace the history of this thermal-like component. Indeed, the thermal emission in GRB 1310… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
51
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 45 publications
(63 citation statements)
references
References 49 publications
12
51
0
Order By: Relevance
“…The C Th spectral shape is usually compatible with a Planck function -based on the quality of the Fermi data. However, a broader spectral shape more compatible with the GRB jet photospheric models was recently reported by Guiriec et al (2015b) who analyzed the spectra of GRB 131014A and showed that it exhibited an intense C Th component. Indeed, while a pure Planck function is well approximated with a cutoff PL (CPL) with an index a Th = +1, the thermal-like component of GRB 131014A is best described with a CPL with an index a » Th +0.6.…”
Section: Introductionsupporting
confidence: 64%
See 2 more Smart Citations
“…The C Th spectral shape is usually compatible with a Planck function -based on the quality of the Fermi data. However, a broader spectral shape more compatible with the GRB jet photospheric models was recently reported by Guiriec et al (2015b) who analyzed the spectra of GRB 131014A and showed that it exhibited an intense C Th component. Indeed, while a pure Planck function is well approximated with a cutoff PL (CPL) with an index a Th = +1, the thermal-like component of GRB 131014A is best described with a CPL with an index a » Th +0.6.…”
Section: Introductionsupporting
confidence: 64%
“…The recent discovery of a thermal-like component, C Th , together with a non-thermal one, C nTh , in the prompt emission of both long (Guiriec et al 2011a(Guiriec et al , 2015a(Guiriec et al , 2015bAxelsson et al 2012) and short (Guiriec et al 2013) GRBs observed with the Fermi Gamma-ray Space Telescope (hereafter, Fermi), challenges the well established Band function paradigm. The C Th spectral shape is usually compatible with a Planck function -based on the quality of the Fermi data.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A further issue arises when one considers that ∝ Γ , with between 2 and 3 in different models [203,208,211]. An explanation could be that direct or Comptonized thermal radiation from the fireball photosphere [208,[210][211][212][213][214][215][216][217][218][219] can affect significantly the GRB prompt emission. This can be a good interpretation of the really energetic spectra presented for many events [220][221][222] and the flat shape in GRB average spectra.…”
Section: Physical Interpretation Of the Energetics Versus Peakmentioning
confidence: 99%
“…The statistical or observational effects could not account for the large scatter of the power law index, and it was suggested to be an intrinsic feature, indicating that no relation common for all GRB pulses peak -peak would be expected. However, in the light of Fermi observations that revealed deviations from the Band function ( [181,[231][232][233][234]; see also [235]), it was proposed recently that the GRB spectra should be modeled not with the Band function itself (constituting a nonthermal component), but with additional blackbody (BB, thermal) and power law (PL, nonthermal) components [216,218,219,236]. The nonthermal component was well described within the context of synchrotron radiation from particles in the jet, while the thermal component was interpreted by the emission from the jet photosphere.…”
Section: Thementioning
confidence: 99%